Sosialisasi Pemrograman Dasar Python di Sekolah SMK Swasta Triyadikayasa Desa Bandar Selamat sebagai Upaya Meningkatkan Literasi Digital dan Kreativitas Siswa: Pengabdian - Mhd Zahir Az Zikri (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The development of information technology requires the younger generation to have adequate digital skills, one of which is through mastery of computer programming. Python was chosen because of its simple syntax but has a wide range of applications. This community service activity, in the form of a socialization of basic Python programming, was held on August 8, 2025, at Triyadikayasa Private Vocational School, Bandar Selamat Village, Aek Songsongan District. The participants were 39 students consisting of Computer Network Engineering (TKJ) and Office Accounting majors. The activity methods included material delivery, hands-on practice, and interactive discussions. The results of the activity showed a significant increase in students' digital literacy, simple code writing skills, and growing interest in exploring the field of information technology. Student enthusiasm was evident through active involvement in practice and discussions, leading to the formation of independent study groups. This activity is a strategic step in improving digital literacy and student creativity, while also providing initial provisions to face the challenges of the digital era.